Analysis of Seasonal Variation in the Vegetation Carbon Flux in Quiterianópolis, Ceará, Brazil (International Journal of Geoscience, Engineering and Technology, 2025)
Vegetation is of significant importance in various ecosystemic, biotic, and abiotic relationships, particularly for its active role in maintaining biogeochemical cycles. A prime example is the carbon cycle, where carbon is removed from the atmosphere and relocated to the biosphere through photosynthesis. Recognizing the importance of vegetation in mitigating the climatic and environmental impacts of carbon, this study aimed to perform a spatial-seasonal analysis of phytomass development, light use efficiency in photosynthesis, and carbon flux for the municipality of Quiterianópolis, Ceará. The analysis was conducted using biophysical indices (NDVI, sPRI, and CO2Flux) derived from Landsat 8 satellite imagery. The findings revealed that climatic seasonality influences the spatial distribution and values of phytomass development, light use efficiency, and carbon assimilation. The variables analyzed during the rainy season were found to be more developed compared to the results from the dry season. This phenomenon is related to the phenological stages of vegetation, which respond to the abiotic stimuli provided by climatic seasonality.